Analisis Sektor Unggulan Dalam Meningkatkan Perekonomian Dan Pembangunan Wilayah Kabupaten Pekalongan Tahun 2011-2015 - Asiyah, Nurul; , Drs. Yuni Prihadi Utomo, MM (2017)
The growth of a sector of the economy that occurred in a region will have an impact only on economic growth refuses in the region, but also in other regions that have economic linkages with the region. The focus of this research is to the determination of the leading economic sector in Pekalongan as consideration in planning economic development. The analysis is the analysis of analisisn typologi, Location Quotien Klassen (LQ), and skalogram analysis. Results klassen typologi shows the sector forward and fast-growing sectors are mining and excavation, the procurement of electricity and gas service sector, Education and health services sectors, social events, and a relatively lagging sectors are construction, transport and warehousing, Real Estate. From the results of LQ shows sector base is electricity and gas Procurement sector, education services, health services and social activities. which sector while the base is the construction sector, transport and warehousing. growth and infrastructure from the skalogram shows sub kedungwuni is central to growth.